Role of Meaningful Social Participation and Technology Use in Mitigating Loneliness and Cognitive Decline Among Older Adults. - Nakahara, Keita; Yokoi, Katsushi (American Journal of Occupational Therapy)
Importance: Community social participation aids dementia prevention and alleviates loneliness among older adults. Incorporating occupational therapy using information and communications technology (ICT) could potentially delay dementia onset and reduce loneliness. Objective: To quantify how meaningful social participation, participation frequency, ICT use, and expanded social networks influence cognitive function and loneliness among socially active older Japanese adults. Design: Cross-sectional exploratory study using structural equation modeling. Setting: Meetings organized by older adults at seven community gathering places in Osaka Prefecture, Japan. Participants: One hundred thirteen healthy older adult cohort members. Measures: Cognitive function assessed via Mini-Cog; loneliness assessed via the condensed UCLA Loneliness Scale. Results: The final model demonstrated excellent fit, χ2(23) = 28.291, p =.205 (root mean square error of approximation =.045, 90% confidence interval [.000,.094]; confirmatory factor index =.995; Tucker–Lewis Index =.993). ICT use directly affected social networks (β = 0.472), which directly influenced participation frequency (β = 0.324) and meaningful social participation (β = 0.381). The indirect effect of meaningful participation significantly improved cognitive function (β = 0.237). The only indirect effect of meaningful interpersonal participation was a reduction in loneliness (β = −0.235). Conclusions and Relevance: ICT use contributes to the expansion of social networks among elderly people. Furthermore, the frequency of social participation and the meaningfulness of such participation are related to reduction in loneliness and maintenance of cognitive function. Although the frequency of social participation was not directly related to these outcomes, the results suggest that meaningful social participation may play an important role in reducing loneliness and maintaining cognitive function. Plain-Language Summary: The promotion of social participation among older people is a global phenomenon, driven by the recognition of its positive relationship with cognitive function and the alleviation of loneliness. Nevertheless, older people's social participation is constrained by a combination of physical and social factors. To address this issue, there has been a push to promote social participation based on information and communications technology (ICT). However, no specific study has been conducted on occupational therapists' perspective in capturing social participation and the use of ICT. The findings of this study show that using ICT has the potential to enhance opportunities for social interaction for older adults, thereby improving the quality and quantity of social participation. The quality of social participation was identified as the sole factor that had a positive impact on cognitive function and loneliness. This study suggests the need for occupational therapists to consider means of facilitating the use of ICTs among older adults as well as interventions that use occupational therapy theory to enhance the meaningfulness of existing social participation opportunities. This study found that using information and communications technology has the potential to enhance opportunities for older adults' social interaction, thereby improving the quality and quantity of social participation.